National myths : constructed pasts, contested presents - Bouchard, Gérard, 1943- (Routledge, 2013)
National myths are now seriously questioned in a number of societies. In the West, for instance, a number of factors have combined to destabilise the symbolic foundation of nations and collective identities. As a result, the diagnosis of a deep cultural crisis has become commonplace. Indeed, who today has not heard about the erosion of common values or the undermining of social cohesion? But to efficiently address this issue, do we know enough about the nature and role of myths in modern and postmodern societies?Against this background, National Myths: Constructed Pasts, Co.